Dermatology Residency Applicant Self-Reported Stressors and Coping Mechanisms by Sex, Race, and Geographic Region during the 2020–2021 Application Cycle. Issue 3 (March 2023) - Tolaymat, Leila M.; Walker, Ashley L.; Yin, Mingyuan; Gillis, Mindy; Haga, Claire; Heckman, Michael; Dawson, Nancy; Hedges, Mary S.
Abstract : This study identifies the self-reported stressors and coping mechanisms of Dermatology residency applicants during the 2020–2021 application cycle, occurring during the coronavirus disease 2019 pandemic. The most common stressors reported were academic, family crisis, and coronavirus disease 2019. The type of stressor differed by race/ethnicity of the applicants and their geographic location. Abstract: Objectives: Our aim was to identify self-reported stressors and coping mechanisms during the 2020–2021 application cycle by dermatology residency applicants. We hypothesized that coronavirus disease 2019 (COVID-19) would be the most reported stressor. Methods: During the 2020–2021 application season, the Mayo Clinic Florida Dermatology residency program sent a supplemental application to each applicant requesting that they describe a challenging life situation and how they handled it. Comparisons of self-reported stressors and self-expressed coping mechanisms according to sex, race, and geographic region were performed. Results: The most common stressors reported were academic (18.4%), family crisis (17.7%), and COVID-19 (10.5%). The most frequent coping mechanisms expressed were perseverance (22.3%), seeking community (13.7%), and resilience (11.5%). The coping mechanism of diligence was observed more often in females than in males (2.8% vs 0.0%, P = 0.045). First in medicine was more often observed in Black or African American students (12.5% vs 0%, P = 0.001), immigrant experience was more often observed in Black or African American and Hispanic students (16.7% and 11.8% vs 3.1%, P = 0.021), and natural disaster was reported more often in Hispanic students (26.5% vs 0.5%, P < 0.001) as compared with White applicants. By geography, applicants in the northeastern United States were more likely to report the COVID-19 pandemic as a stressor (19.5%, P = 0.049), and the natural disaster stressor was more often reported by applicants from outside the continental United States (45.5%, P < 0.001). Conclusions: Stressors reported by dermatology applicants in the 2020–2021 cycle included academic, family crisis, and the COVID-19 pandemic. The type of stressor reported varied by race/ethnicity and geographic location of the applicant.